Eltrombopag treatment for severe immune thrombocytopenia during pregnancy: a case report. Issue 7 (October 2021) - Mendicino, Francesco; Santoro, Cristina; Martino, Enrica; Botta, Cirino; Baldacci, Erminia; Ferretti, Antonietta; Muto, Brunella; Lucia, Eugenio; Caracciolo, Daniele; Vigna, Ernesto; Morelli, Michele; Gentile, Massimo
Abstract : N/A: Primary immune thrombocytopenia (ITP) is an autoimmune disorder characterized by isolated thrombocytopenia (platelet count <100 × 10 9 /l) in the absence of other causes or disorders associated. The incidence of ITP in pregnancy is one to two cases per 1000 gestations. ITP could be diagnosed before or during pregnancy; sometimes a relapse of a previously diagnosed ITP can occur. Intravenous immune globulins (IVIg) and corticosteroids are the standard frontline therapy because of their well known safety profile either for the mother or for the neonate. Treatments for refractory patients are limited by potential fetal risk. We report the case of a patient with ITP along pregnancy, refractory to corticosteroids and IVIg, successfully treated with, the thrombopoietin receptor agonist (TPO-RA) eltrombopag. Patient received this compound for almost the whole pregnancy and in particular for the whole first trimester, without any complication for the mother and the neonate. Although transient administration of TPO-RAs in pregnancy seems to be well tolerated, their use during the whole gestation is still controversial; this is the reason of the description of this case, which did not show any complications, and thus it could add useful information on this field.